1997
DOI: 10.1016/s1071-3581(97)90043-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of resting regional wall thickening and stress perfusion with electrocardiographic-gated technetium 99m-labeled sestamibi single-photon emission computed tomography: Prediction of stress defect reversibility

Abstract: Visual evidence of wall thickening by poststress ECG-gated SPECT sestamibi imaging in the territory of a stress-induced perfusion defect correlates highly with stress defect reversibility on rest imaging and may obviate the need to perform rest imaging, thereby potentially reducing the time and cost involved in myocardial perfusion imaging. The absence of visually apparent wall thickening, however, underestimates the prevalence of stress defect reversibility on rest imaging; in such instances, rest imaging mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Marzullo et al [17] and few other groups [2,6,7,[18][19][20] used ECG-gated post-stress 99m Tc-MIBI images for the detection of wall motion abnormalities and reversibility of stress induced perfusion defects. The common advantage in all these studies was the use of single injection as well as single image acquisition for the detection of CAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marzullo et al [17] and few other groups [2,6,7,[18][19][20] used ECG-gated post-stress 99m Tc-MIBI images for the detection of wall motion abnormalities and reversibility of stress induced perfusion defects. The common advantage in all these studies was the use of single injection as well as single image acquisition for the detection of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The common advantage in all these studies was the use of single injection as well as single image acquisition for the detection of CAD. Although most of these studies have reported a good accuracy for the diagnosis of CAD by single-phase stress gated SPECT [17,20], a few others have revealed some conflicting results, particularly in patients with pasthistory of myocardial infarction [6,7]. One of the main reasons for such conflicts is the presence of myocardial stunning or hibernation, which results in abnormal myocardial motion/thickening with normal or abnormal perfusion [2,13,19,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gated myocardial perfusion SPET with 99m Tc-MIBI has been proposed as a method to identify viable myocardium [4,7]. The relative preservation of wall thickening in the area of perfusion defects may be the result of the maintenance of regional function despite chronic ischaemia or repeated stunning.…”
Section: Discussionmentioning
confidence: 99%
“…Snapper et al [7] concluded that visual evidence of wall thickening on post-stress 99m Tc-MIBI ECG-gated SPET imaging in the territory of a stress-induced perfusion defect correlates highly with stress defect reversibility on rest imaging and that this may obviate the need to perform rest imaging. This correlation potentially reduces the time for resting perfusion SPET.…”
Section: Comparison Of Single-injection Stress 99m Tc-mibi Gated Spetmentioning
confidence: 99%